La fusión del community manager y periodista en pro de la comunicación virtual en la productora de televisión JD producciones en Guayaquil - Cruz Torres, Karla Ninoska (2016)
This research had as main purpose to analyze the development and role of a Community Manager within a media, specifically investigate how it works and how does the virtual community manager at JD Productions television production function. This analysis is important to determine the professional roles between a journalist and community manager is the best choice to benefit virtual communication, as many times the Community Manager of a media does not know anything about journalism and there when there are many mistakes and weaknesses that are reflected in web pages or social networking medium…..